The joint distribution of net worth and pension wealth in Germany - Timm Bönke; Markus M. Grabka; Carsten Schröder; Edward N. Wolff; Lennard Zyska (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
Research on wealth inequality usually focuses on real and financial assets, while pension wealth - the present value of future pension entitlements from public and company pension schemes - receives little attention. This is astonishing, given that pension plans play an important role for material security and well-being for an overwhelming part of the population and, thus, should be accounted for in peoples' wealth portfolios. Using novel data from the Socio Economic Panel (SOEP), we show the incidence, relevance, and distribution of individual pension wealth, net worth, and augmented wealth (the sum of the two) in Germany. Further, we investigate age-wealth-profiles and differences between East and West Germany.
Keywords: D31; H55; J32; 330; net worth; pension wealth; augmented wealth; SOEP; age wealth profiles